الاشتراطات البيئية وتنافسية الصادرات السلعية لقطاع الصناعة في الدول النامية -دراسة قياسية للفترة 2005-2020 - غانية, نذير; هميسي, كوثر (جامعة الوادي - University of Eloued, 2022)
: تهدف هذه الدراسة إلى قياس أثر الاشتراطات البيئية على تنافسية الصادرات السلعية لقطاع الصناعة لمجموعة من الدول النامية، وذلك باستخدام نموذج Panel ARDL- PMG للفترة 2005-2020، ولتحقيق هذا الهدف تم الاعتماد على أهم المتغيرات البيئية والاقتصادية التي يمكن أن تكون لها ذات تأثير مباشر لان لم تعتمد على التأثير المباشر وغير المباشر على تنافسية الصادرات السلعية، حيث تم التعبير عن تنافسية الصادرات السلعية لقطاع الصناعة بمعدل الصادرات السلعية الصناعية كمتغير تابع، في حين تم التعبير عن الاشتراطات البيئية بانبعاثات غاز ثاني أكسيد الكربون كمتغير مستقل، بالإضافة إلى إدراج متغيرات اقتصادية أخرى ذات علاقة بالمتغير التابع كما ذكرنا وهي الناتج المحلي الاجمالي، مؤشر سعر الصرف الفعلي الحقيقي، معدل درجة حرية التجارة، ومعدل التعريفة الجمركية على المنتجات. وبناء على نتائج تقدير النموذج توصلت الدراسة إلى أن انبعاثات غاز ثاني أكسيد الكربون تربطها علاقة عكسية ومعنوية إحصائيا مع الصادرات السلعية الصناعية في المدى القصير، وعلاقة طردية ولكنها غير معنوية إحصائيا في المدى الطويل ،ويفسر هذا اقتصاديا انه في المدى القصير يتفق الوضع مع فرضية ملاذ التلوث التي تقول ان السياسات والمعايير البيئية تعرقل كل من التجارة الصادرات أما في المدى الطويل فان نتيجة تتفق مع فرضية بورتر بانه على المدى الطويل تصبح الشركات والدول تطبق في المعايير والسياسات البيئية وهذا حتى ينزع عنها ما يسمى تكاليف الامتثال البيئي . This study aims to measure the impact of environmental requirements on the competitiveness of merchandise exports to the industrial sector for a group of developing countries, using the Panel ARDL-PMG model for the period 2005-2020. It did not depend on the direct and indirect impact on the competitiveness of merchandise exports, as the competitiveness of merchandise exports to the industry sector was expressed in the rate of industrial merchandise exports as a dependent variable, while the environmental requirements were expressed in carbon dioxide emissions as an independent variable, In addition to the inclusion of other economic variables related to the dependent variable, as we mentioned, which are the gross domestic product, the real effective exchange rate index, the rate of the degree of freedom of trade, and the rate of customs tariffs on . product s Based on the results of estimating the model, the study concluded that carbon dioxide emissions have a statistically inverse and significant relationship with industrial commodity exports in the short term, and a direct relationship, but it is not statistically significant in the long term, and this explains economically that in the short term the situation agrees With the pollution haven hypothesis, which says that environmental policies and standards impede both trade and exports, but in the long run, the result is consistent with Porter's hypothesis that in the long run, companies and countries apply in environmental standards and policies, and this is until the so-called environmental compliance costs are removed from them
Environmental requirements and the competitiveness of merchandise exports for the industrial sector A standard study for a group of developing countries for the period from 2005 to 2020
Keywords: تنافسية الصادرات السلعية ؛ انبعاثات غاز أكسيد ثاني الكربون ؛ بيانات البانل